A new cone-shaped aortic valve prosthesis for orthotopic position: an experimental study in Swine - Sochman, Jan; Peregrin, Jan H; Pulda, Zdenek; Pavcnik, Dusan; Uchida, Barry T; Timmermans, Hans A; Rösch, Josef (Cardiovascular and interventional radiology, 2010)
The aim of this experimental study was to evaluate a newly designed cone-shaped aortic valve prosthesis (CAVP) for one-step transcatheter placement in an orthotopic position. The study was conducted in 15 swine using either the transcarotid (11 animals) or the transfemoral (4 animals) artery approach. A 12- or 13-Fr sheath was inserted via arterial cutdown. The CAVP was deployed under fluoroscopic control and its struts, by design, induced significant native valve insufficiency. CAVP function was evaluated by aortography and aortic pressure curve tracing. In 11 of 15 swine the CAVP was properly deployed and functioned well throughout the scheduled period of 2-3 h. In three swine the CAVPs were placed lower than intended, however, they were functional even in the left ventricular outflow tract position. One swine expired due to inadvertent low CAVP placement that caused both aortic regurgitation and immobilization of the anterior mitral valve leaflet by the valve struts. We conclude that this design of CAVP is relatively easy to deploy, works well throughout a short time period (2-3 h), and, moreover, seems to be reliable even in a lower-than-orthotopic position (e.g., infra-annulary space). Longer-term studies are needed for its further evaluation.
Keywords: náhodné rozdělení; aortální insuficience; senzitivita a specificita; Sensitivity and Specificity; bioprotézy; Female; chirurgická náhrada chlopně; Femoral Artery; angiografie; zvířata; Heart Valve Prosthesis; Prosthesis Design; Swine; Carotid Arteries; Angiography; ženské pohlaví; Bioprosthesis; Male; Aortic Valve Insufficiency; srdeční katetrizace; Cardiac Catheterization; arteria femoralis; srdeční chlopně umělé; Animals; Risk Assessment; protézy - design; mužské pohlaví; Disease Models, Animal; Random Allocation; Heart Valve Prosthesis Implantation; hodnocení rizik; prasata; arteriae carotides; modely nemocí na zvířatech